TRENDS AND INSIGHTS: A BIBLIOMETRIC ANALYSIS OF STUNTING POLICY RESEARCH IN THE SCOPUS DATABASE (2000-2023) - Puspita, Dian Permata; Jatnika, Dyana Chusnulitta; A. Tadda, Muh. Rivaldi (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the bibliographic characteristics and content of stunting policy articles published in Scopus indexed journals by researchers around the world from 2000 to 2023. Data was taken from the Scopus database using the search term